Climate and archetype: vernacular house-forms as tropical urban ideations - Mohd Nawawi, Norwina; Shamsudin, Shaiful Nadzri (Palgrave Macmillan, 2023)
The rise of the sustainable agenda must face the reality of tropical regions, which must grow their own archetypes and models of sustainable urbanism. Urban principles derived from the local vernacular roots can contribute to the agenda of lowering carbon emissions in a congested city based on local conceptualisations derived from the region. To explore ideations within the local Malay form, one must develop structural and spatial vocabularies that can feed into urban design concepts that can evoke later historical and cultural forms, which coincide with the goals of green urbanism and the low carbon agenda.